Radiation refrigeration glaze, preparation method thereof and lightweight ceramic tile

By applying radiation refrigeration glaze of nanoporous alumina and metal oxide-doped magnesium aluminum spinel on the surface of lightweight ceramic tiles, the problem of difficulty in reducing the temperature in the building is solved, and efficient radiation refrigeration effect and low energy consumption are achieved.

CN119591321AActive Publication Date: 2025-03-11FOSHAN OCEANO CERAMICS

Patent Information

Application Number
CN202411788031.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the temperature in buildings, reduce the dependence on refrigeration equipment and the problem of high energy consumption.

Method used

By applying a radiation refrigeration glaze including nanoporous alumina and metal oxide-doped magnesium aluminum spinel on the surface of the lightweight ceramic tiles, the sunlight reflectivity of the glaze surface is improved, and the radiation refrigeration effect is achieved.

Benefits of technology

It achieves a good radiation refrigeration effect, with a reflectivity of sunlight up to 88-94%, while ensuring glaze quality and brick shape, reducing the frequency of use and energy consumption of refrigeration equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174594810000071
    Figure BDA0005174594810000071
Patent Text Reader

Abstract

The invention belongs to the technical field of architectural ceramics, and particularly discloses radiation refrigeration glaze, a preparation method thereof and a lightweight ceramic tile. The radiation refrigeration glaze comprises a basic glaze and radiation refrigeration powder, the radiation refrigeration powder comprises nano-porous alumina and metallic oxide doped magnesium aluminate spinel, and the metallic oxide is selected from at least one of iron sesquioxide, manganese dioxide, cobalt sesquioxide and copper oxide. According to the invention, nano-porous alumina and metallic oxide doped magnesium aluminate spinel are compounded as radiation refrigeration powder, and the radiation refrigeration powder is added into the cover glaze of the light ceramic tile, so that not only are good glaze quality and tile shape obtained, but also the sunlight reflectivity ratio of the glaze is improved, thereby achieving a good radiation refrigeration effect, and improving the service life of the light ceramic tile. The sunlight reflectivity reaches up to 88-94%, the glaze quality and the brick shape are good, and the surface flatness is + / -0.3 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building ceramics, and in particular relates to a radiation cooling glaze and a preparation method thereof, and a lightweight ceramic tile. Background Art

[0002] With the development of economy and society, people are increasingly dependent on indoor environment and spend more and more time indoors. According to statistics from relevant institutions, urban residents in my country spend more than 80% of their time indoors every day. With the development of social economy and people's increasing requirements for indoor environmental comfort, the requirements for buildings are also increasing rapidly, especially in the hot summer. Many cities have heat island effects, and the temperature in cities is generally about 5°C higher than that in suburbs. This leads to increasing dependence on the use of refrigeration equipment and increasing energy consumption. In order to reduce the use of refrigeration equipment and alleviate the high energy consumption of refrigeration equipment, it is urgent to develop energy-saving and environmentally friendly refrigeration technology.

[0003] Lightweight ceramic tiles are porous, lightweight, and heat-insulating. They are a new generation of green, energy-saving, and environmentally friendly building materials that can effectively reduce the load on the floor. At the same time, their good heat-insulating properties can be used as building energy-saving materials to reduce electricity consumption. Therefore, they can be widely used in interior and exterior walls of buildings. Radiative cooling materials mainly control the optical properties of the surface of objects, reflect solar heat, and use atmospheric windows to continuously radiate heat to high altitudes, thereby effectively reducing the surface temperature of objects and achieving a low-energy cooling effect. Therefore, applying a layer of radiative cooling glaze on the surface of lightweight ceramic tiles is an effective means to alleviate the high energy consumption of refrigeration equipment. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a radiation cooling glaze and a preparation method thereof, and a lightweight ceramic tile. When the radiation cooling glaze is applied to a lightweight body, the solar reflectivity of the glaze surface can be effectively improved while ensuring the glaze surface quality and brick shape, thereby achieving a good radiation cooling effect.

[0005] To solve the above technical problems, the first aspect of the present invention provides a radiation refrigeration glaze, including a basic glaze and a radiation refrigeration powder, wherein the radiation refrigeration powder includes nanoporous alumina and magnesium aluminate spinel doped with metal oxides, and the metal oxides are selected from at least one of ferric oxide, manganese dioxide, cobalt oxide, and copper oxide.

[0006] Specifically, nanoporous alumina has a high infrared reflectivity. When infrared light hits the surface of nanoporous alumina, part of the light will be reflected back, while the other part will penetrate into the particles. Inside the particles, the light will be reflected and refracted multiple times. Due to the high reflectivity of alumina, most of the light inside the particles will also be reflected back. Therefore, during the radiation cooling process, nanoporous alumina can release heat in the form of infrared radiation through the atmospheric window, thereby achieving its own cooling effect. However, due to the sintering temperature and expansion coefficient of nanoporous alumina (8.0×10 -6 -9.3×10 -6 K -1 ) are relatively high. If it is directly added to the glaze, when the dosage is too low, it will not achieve a good infrared light reflection effect; when the dosage is too high, on the one hand, it will easily lead to insufficient firing of the glaze, affecting the glaze effect of the ceramic tile; on the other hand, it will cause the glaze to be fired due to the thermal expansion coefficient of the lightweight body (7.3×10 -6 -7.6×10 -6 K -1 ) do not match and deform.

[0007] Based on this, the present invention uses nanoporous alumina and metal oxide doped magnesium aluminum spinel compound as radiation refrigeration powder, and magnesium aluminum spinel can be used as a raw material for preparing ceramic glaze, which not only does not have a negative impact on the glaze, but also is conducive to improving the mechanical properties of the glaze; at the same time, magnesium aluminum spinel itself has certain optical properties, and after being doped with ferric oxide, manganese dioxide, cobalt oxide and copper oxide, iron ions, manganese ions, cobalt ions and copper ions enter the crystal structure of spinel, replacing part of magnesium ions or aluminum ions, changing the original structure of the crystal, forming doped magnesium aluminum spinel, and greatly enhancing the light reflection effect of magnesium aluminum spinel; and the doped magnesium aluminum spinel also has a lower melting point, and adding it to the glaze can effectively reduce the firing temperature of the glaze; in addition, the thermal expansion coefficient of the metal oxide doped magnesium aluminum spinel (6.0×10 -6 -6.8×10 -6 K -1 ) is low, which can effectively balance the difference in thermal expansion coefficient between nanoporous alumina and lightweight body. Therefore, the present invention replaces part of nanoporous alumina with metal oxide-doped magnesium aluminum spinel, which not only obtains good glaze quality and brick shape, but also improves the solar reflectivity of the glaze, thereby achieving a good radiation cooling effect.

[0008] In some embodiments of the present invention, the doping amount of the metal oxide is 0.3-1 wt%. Ferrous oxide, manganese dioxide, cobalt oxide, and copper oxide are all non-ferrous metal oxides, and their content in the glaze should not be too high.

[0009] In some embodiments of the present invention, the particle size of the nanoporous alumina is 20-50 nm.

[0010] In some embodiments of the present invention, the pore size of the nanoporous alumina is 2-20 nm.

[0011] In some embodiments of the present invention, the specific surface area of ​​the nanoporous alumina is 200-300 m 2 / g. Nano-alumina with high specific surface area is not only beneficial to improving the infrared light reflectivity of alumina, but also beneficial to reducing the sintering temperature of alumina.

[0012] In some embodiments of the present invention, the mass ratio of nanoporous alumina in the radiation cooling powder is 50-70%. By adjusting the mass ratio of nanoporous alumina to metal oxide-doped magnesium aluminum spinel, the infrared light reflectivity of the glaze is improved while ensuring the glaze quality and brick shape.

[0013] In some embodiments of the present invention, the mass ratio of the basic glaze to the radiation cooling powder is 100:(5-20). A certain amount of radiation cooling powder is added to the glaze to improve the infrared light reflectivity of the glaze without affecting the performance of the glaze.

[0014] In some embodiments of the present invention, the raw materials for preparing the basic glaze include, by weight: 20-25 parts of feldspar powder, 25-30 parts of calcined kaolin, 20-25 parts of quartz, 3-5 parts of talc, 2-5 parts of calcium carbonate, 2-5 parts of dolomite, and 3-5 parts of borax.

[0015] The second aspect of the present invention provides a method for preparing the above-mentioned radiation cooling glaze, comprising the following steps:

[0016] The basic glaze and the radiation refrigeration powder are wet-milled to obtain the radiation refrigeration glaze.

[0017] In some embodiments of the present invention, the specific gravity of the radiation cooling glaze is 1.8-1.9 g / cm 3 .

[0018] A third aspect of the present invention provides a lightweight ceramic tile, comprising a lightweight body and a surface glaze layer, wherein the surface glaze layer is fired from the above-mentioned radiation cooling glaze.

[0019] In some embodiments of the present invention, the raw materials for preparing the lightweight green body include silicon carbide.

[0020] Specifically, when lightweight ceramic tiles are fired at high temperatures, silicon carbide reacts to produce CO2 gas, a portion of which forms a closed-cell structure in the ceramic tile, while the other portion overflows through the surface glaze layer, which easily leads to defects such as pinholes and bubbles on the glaze surface, affecting the glaze quality of the ceramic tile. The nanoporous alumina in the radiant cooling glaze of the present invention is conducive to improving the sealing effect of CO2 gas and reducing the generation of glaze defects.

[0021] In some embodiments of the present invention, the volume density of the lightweight ceramic brick is 1.7-1.9 g / cm 3 .

[0022] In some embodiments of the present invention, the maximum firing temperature is 1150-1250°C.

[0023] In some embodiments of the present invention, the firing period is 50-80 minutes.

[0024] In some embodiments of the present invention, a protective glaze layer is further provided on the surface of the surface glaze layer.

[0025] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:

[0026] (1) The present invention uses nanoporous alumina and metal oxide doped magnesium aluminum spinel as radiation cooling powder, and adds it to the surface glaze of lightweight ceramic tiles, which not only obtains good glaze quality and brick shape, but also improves the solar reflectivity of the glaze, thereby achieving a good radiation cooling effect. Among them: nanoporous alumina has a high infrared reflectivity. During the radiation cooling process, heat can be released in the form of infrared radiation through the atmospheric window, thereby achieving its own cooling effect. Magnesium aluminum spinel can be used as a raw material for preparing ceramic glazes, which not only does not have a negative impact on the glaze, but also helps to improve the mechanical properties of the glaze; doped metal oxides such as ferric oxide, manganese dioxide, cobalt oxide, and copper oxide are all reflective raw materials. These metal oxides can emit the absorbed sunlight and heat into the air at a certain wavelength, playing a blocking and reflecting role; at the same time, the doped metal oxides have a lower melting temperature, which can effectively reduce the firing temperature of the glaze; in addition, the metal oxide doped magnesium aluminum spinel has a lower thermal expansion coefficient, which can effectively balance the difference in thermal expansion coefficient between the nanoporous alumina and the blank.

[0027] (2) The lightweight ceramic bricks prepared by the present invention have good radiation cooling function, the solar reflectivity is as high as 88-94%, and the glaze quality and brick shape are good, and the surface flatness is ±0.3mm. DETAILED DESCRIPTION

[0028] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0029] The raw material components of the green body used in the following examples and comparative examples include, by weight: 45 parts of feldspar, 18 parts of clay, 8 parts of ball clay, 5 parts of talc, 5 parts of bentonite, 12 parts of quartz, and 0.5 parts of silicon carbide.

[0030] The chemical composition of the protective glaze includes, by weight percentage: 57% SiO2, 33% Al2O3, 0.1% Fe2O3, 0.2% TiO2, 0.4% CaO, 0.4% MgO, 2% K2O, 1% Na2O, 1% ZrO2 and 5% loss on ignition.

[0031] Example 1

[0032] A radiation cooling glaze, the raw material components of which include by weight: 20 parts of feldspar powder, 30 parts of calcined kaolin, 25 parts of quartz, 5 parts of talc, 5 parts of calcium carbonate, 2 parts of dolomite, 3 parts of borax, and 10 parts of radiation cooling powder. The radiation cooling powder includes 6 parts of porous nano-alumina and 4 parts of ferric oxide-doped magnesium aluminum spinel. The particle size of the porous nano-alumina is 20-50nm, the pore size is 2-20nm, and the specific surface area is 220m 2 / g; the doping amount of ferric oxide is 0.5wt%.

[0033] A method for preparing a lightweight ceramic tile comprises the following steps:

[0034] (1) weighing raw materials according to the raw material components of the lightweight green body, preparing powder, distributing, dry pressing and drying to obtain the lightweight green body;

[0035] (2) The raw materials for preparing the radiation cooling glaze are weighed according to the weight ratio, and wet ball milled to obtain a glaze with a specific gravity of 1.8 g / cm 3 Radiant cooling glaze;

[0036] (3) Weigh the raw materials according to the chemical composition of the protective glaze, and wet ball grind them to obtain a glaze with a specific gravity of 1.9 g / cm 3 protective glaze;

[0037] (4) The radiation cooling glaze (glazing thickness is 0.5 mm) and the protective glaze (glazing thickness is 0.3 mm) are sequentially applied on the surface of the lightweight body prepared as above to form a surface glaze layer and a protective glaze layer in turn. After drying and firing (the maximum firing temperature is 1150°C and the firing cycle is 60 minutes), the lightweight ceramic brick of this embodiment is obtained.

[0038] Example 2

[0039] A radiation cooling glaze, the raw material components of which include by weight: 20 parts of feldspar powder, 25 parts of calcined kaolin, 25 parts of quartz, 5 parts of talc, 5 parts of calcium carbonate, 2 parts of dolomite, 3 parts of borax, and 15 parts of radiation cooling powder. The radiation cooling powder includes 10.5 parts of porous nano-alumina and 4.5 parts of manganese dioxide-doped magnesium aluminum spinel. The particle size of the porous nano-alumina is 20-50nm, the pore size is 2-20nm, and the specific surface area is 250m 2 / g; the doping amount of manganese dioxide is 0.6wt%.

[0040] A method for preparing a lightweight ceramic tile comprises the following steps:

[0041] (1) weighing raw materials according to the raw material components of the lightweight green body, preparing powder, distributing, dry pressing and drying to obtain the lightweight green body;

[0042] (2) The raw materials for preparing the radiation cooling glaze are weighed according to the weight ratio, and wet ball milled to obtain a glaze with a specific gravity of 1.8 g / cm 3 Radiant cooling glaze;

[0043] (3) Weigh the raw materials according to the chemical composition of the protective glaze, and wet ball grind them to obtain a glaze with a specific gravity of 1.9 g / cm 3 protective glaze;

[0044] (4) A radiation cooling glaze (glazing thickness is 0.7 mm) and a protective glaze (glazing thickness is 0.2 mm) are sequentially applied on the surface of the lightweight body prepared as described above to form a surface glaze layer and a protective glaze layer in turn. After drying and firing (the maximum firing temperature is 1200°C and the firing cycle is 60 minutes), the lightweight ceramic brick of this embodiment is obtained.

[0045] Example 3

[0046] A radiation cooling glaze, the raw material components of which include by weight: 20 parts of feldspar powder, 25 parts of calcined kaolin, 25 parts of quartz, 5 parts of talc, 5 parts of calcium carbonate, 5 parts of dolomite, 5 parts of borax, and 10 parts of radiation cooling powder. The radiation cooling powder includes 6 parts of porous nano-alumina and 4 parts of cobalt trioxide-doped magnesium aluminum spinel. The particle size of the porous nano-alumina is 20-50nm, the pore size is 2-20nm, and the specific surface area is 250m 2 / g; the doping amount of cobalt trioxide is 0.6wt%.

[0047] A method for preparing a lightweight ceramic tile comprises the following steps:

[0048] (1) weighing raw materials according to the raw material components of the lightweight green body, preparing powder, distributing, dry pressing and drying to obtain the lightweight green body;

[0049] (2) The raw materials for preparing the radiation cooling glaze were weighed according to the weight ratio, and wet ball milled to obtain a glaze with a specific gravity of 1.9 g / cm 3 Radiant cooling glaze;

[0050] (3) Weigh the raw materials according to the chemical composition of the protective glaze, and wet ball grind them to obtain a glaze with a specific gravity of 1.9 g / cm 3 protective glaze;

[0051] (4) The radiation cooling glaze (glazing thickness is 0.5 mm) and the protective glaze (glazing thickness is 0.3 mm) are sequentially applied on the surface of the lightweight body prepared as above to form a surface glaze layer and a protective glaze layer in turn. After drying and firing (the maximum firing temperature is 1200°C and the firing cycle is 70 minutes), the lightweight ceramic brick of this embodiment is obtained.

[0052] Example 4

[0053] A radiation cooling glaze, the raw material components of which include by weight: 20 parts of feldspar powder, 25 parts of calcined kaolin, 20 parts of quartz, 5 parts of talc, 5 parts of calcium carbonate, 5 parts of dolomite, 5 parts of borax, and 15 parts of radiation cooling powder. The radiation cooling powder includes 9 parts of porous nano-alumina and 6 parts of copper oxide-doped magnesium aluminum spinel. The particle size of the porous nano-alumina is 20-50nm, the pore size is 2-20nm, and the specific surface area is 240m 2 / g; the doping amount of copper oxide is 0.5wt%.

[0054] A method for preparing a lightweight ceramic tile comprises the following steps:

[0055] (1) weighing raw materials according to the raw material components of the lightweight green body, preparing powder, distributing, dry pressing and drying to obtain the lightweight green body;

[0056] (2) The raw materials for preparing the radiation cooling glaze are weighed according to the weight ratio, and wet ball milled to obtain a glaze with a specific gravity of 1.8 g / cm 3 Radiant cooling glaze;

[0057] (3) Weigh the raw materials according to the chemical composition of the protective glaze, and wet ball grind them to obtain a glaze with a specific gravity of 1.9 g / cm 3 protective glaze;

[0058] (4) The radiation cooling glaze (glazing thickness is 0.5 mm) and the protective glaze (glazing thickness is 0.3 mm) are sequentially applied on the surface of the lightweight body prepared as above to form a surface glaze layer and a protective glaze layer in turn. After drying and firing (the maximum firing temperature is 1200°C and the firing cycle is 60 minutes), the lightweight ceramic brick of this embodiment is obtained.

[0059] Comparative Example 1

[0060] The difference between Comparative Example 1 and Example 1 is that the raw material components of the radiation refrigeration glaze are different. The radiation refrigeration powder in the raw material components of the radiation refrigeration glaze of Comparative Example 1 is a single porous nano-alumina. The raw material components of the radiation refrigeration glaze of Comparative Example 1 include, by weight: 20 parts of feldspar powder, 30 parts of calcined kaolin, 25 parts of quartz, 5 parts of talc, 5 parts of calcium carbonate, 2 parts of dolomite, 3 parts of borax, and 10 parts of radiation refrigeration powder. Among them: the radiation refrigeration powder is porous nano-alumina, with a particle size of 20-50nm, a pore size of 2-20nm, and a specific surface area of ​​220m 2 / g.

[0061] The preparation method of the lightweight ceramic brick of Comparative Example 1 is the same as that of Example 1.

[0062] Comparative Example 2

[0063] The difference between Comparative Example 2 and Example 1 is that the raw material components of the radiation refrigeration glaze are different. The radiation refrigeration powder in the raw material components of the radiation refrigeration glaze of Comparative Example 2 is a single magnesium aluminum spinel doped with iron trioxide. The raw material components of the radiation refrigeration glaze of Comparative Example 2 include, by weight: 20 parts of feldspar powder, 30 parts of calcined kaolin, 25 parts of quartz, 5 parts of talc, 5 parts of calcium carbonate, 2 parts of dolomite, 3 parts of borax, and 10 parts of radiation refrigeration powder. Among them: the radiation refrigeration powder is magnesium aluminum spinel doped with iron trioxide, and the doping amount of iron trioxide is 0.5wt%.

[0064] The preparation method of the lightweight ceramic brick of Comparative Example 2 is the same as that of Example 1.

[0065] Comparative Example 3

[0066] The difference between Example 3 and Example 1 is that the raw material components of the radiation refrigeration glaze are different. The radiation refrigeration powder in the raw material components of the radiation refrigeration glaze of Example 3 includes 6 parts of porous nano alumina and 4 parts of zinc oxide-doped magnesium aluminum spinel. The raw material components of the radiation refrigeration glaze of Example 4 include, by weight: 20 parts of feldspar powder, 30 parts of calcined kaolin, 25 parts of quartz, 5 parts of talc, 5 parts of calcium carbonate, 2 parts of dolomite, 3 parts of borax, and 10 parts of radiation refrigeration powder. Among them: the particle size of the porous nano alumina is 20-50nm, the pore size is 2-20nm, and the specific surface area is 200-300m 2 / g; the doping amount of zinc oxide is 0.5wt%.

[0067] The preparation method of the lightweight ceramic brick of Comparative Example 3 is the same as that of Example 1.

[0068] Performance Testing

[0069] The volume density, solar reflectance ratio and surface smoothness of the lightweight ceramic tile samples prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-3 were tested, and the glaze quality was observed. Wherein: The solar reflectance test is based on Part 1 of the standard GJB5023.1A-2012 Test Method for Reflectance and Emissivity of Materials and Coatings. Reflectance refers to the proportion of solar radiation reflected by the surface of the material, usually expressed as a percentage. The higher the reflectance, the less solar energy absorbed by the surface and the lower the surface temperature. The surface smoothness is tested in accordance with GB / T 4100-2015 "Ceramic Tiles", measuring the center curvature of the sample relative to the diagonal calculated by the working size; the size of the sample is 400×800mm, and the test results are shown in Table 1.

[0070] Table 1:

[0071]

[0072] It can be seen from Table 1 that the lightweight ceramic tile samples prepared in Examples 1-4 all have good radiation cooling effects, with a solar reflectivity of 88-94%; the tile surface has high flatness; and the glaze surface has good quality without obvious defects.

[0073] Comparative Example 1 Compared with Example 1, the radiation cooling powder uses a single porous nano-alumina, and the thermal expansion coefficient of the surface glaze layer is excessively greater than the thermal expansion coefficient of the lightweight body. During the cooling process, the lightweight body is subjected to the compressive stress of the surface glaze layer, while the surface glaze layer is subjected to the tensile stress of the lightweight body, resulting in the brick body warping upward and severe concave deformation. The solar reflectivity and flatness of the glaze surface cannot be tested, and the glaze surface cracks.

[0074] Comparative Example 2 Compared with Example 1, the radiation cooling powder uses a single iron oxide-doped magnesium aluminum spinel, and the thermal expansion coefficient of the surface glaze layer is slightly smaller than that of the lightweight body. During the cooling process, the surface glaze layer is subjected to the compressive stress of the lightweight body, while the lightweight body is subjected to the tensile stress of the surface glaze layer, resulting in the brick body bending downward and convex deformation, and the solar reflectivity and flatness of the glaze cannot be tested. At the same time, due to the reduction of alumina content, the bubbles generated in the lightweight body cannot be sealed in the brick body, resulting in defects such as pinholes and glaze bubbles on the glaze surface.

[0075] In Comparative Example 3, relative to Example 1, the radiant refrigeration powder uses zinc oxide-doped magnesium aluminum spinel instead of iron oxide-doped magnesium aluminum spinel. Since zinc oxide-doped magnesium aluminum spinel reduces the reflectivity in the visible light range and enhances the absorption of visible light, the solar reflectivity of the glaze is significantly lower than that of Example 1.

[0076] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.

Claims

1. A radiation cooling glaze, characterized in that: The invention comprises a basic glaze and a radiation refrigeration powder, wherein the radiation refrigeration powder comprises nanoporous alumina and magnesium-aluminum spinel doped with metal oxides, and the metal oxides are selected from at least one of ferric oxide, manganese dioxide, cobalt oxide and copper oxide.

2. The radiant cooling glaze according to claim 1, characterized in that: The doping amount of the metal oxide is 0.3-1 wt %.

3. The radiant cooling glaze according to claim 1, characterized in that: The particle size of the nanoporous alumina is 20-50 nm; and / or, the pore size of the nanoporous alumina is 2-20 nm; and / or, the specific surface area of ​​the nanoporous alumina is 200-300 m 2 / g.

4. The radiant cooling glaze according to claim 1, characterized in that: In the radiation refrigeration powder, the mass proportion of nanoporous alumina is 50-70%.

5. The radiant cooling glaze according to claim 1, characterized in that: The mass ratio of the basic glaze to the radiation refrigeration powder is 100:(5-20).

6. The radiant cooling glaze according to claim 1, characterized in that: The raw materials for preparing the basic glaze include, by weight: 20-25 parts of feldspar powder, 25-30 parts of calcined kaolin, 20-25 parts of quartz, 3-5 parts of talc, 2-5 parts of calcium carbonate, 2-5 parts of dolomite, and 3-5 parts of borax.

7. A method for preparing the radiation cooling glaze according to claims 1-6, characterized in that: The following steps are involved: The basic glaze and the radiation refrigeration powder are wet-milled to obtain the radiation refrigeration glaze.

8. The method for preparing the radiation cooling glaze according to claim 7, characterized in that: The specific gravity of the radiation cooling glaze is 1.8-1.9 g / cm 3 .

9. A lightweight ceramic tile, characterized in that: The invention comprises a lightweight body and a surface glaze layer, wherein the surface glaze layer is formed by firing the radiation cooling glaze according to any one of claims 1 to 6.

10. The lightweight ceramic tile according to claim 9, characterized in that: The maximum firing temperature is 1150-1250° C.; and / or the firing period is 50-80 minutes.

Citation Information

Patent Citations

  • Nanometer reflective heat-insulation coating for exterior wall and preparation technique thereof

    CN104877474A

  • Reflective type radiation refrigerating material, reflective type radiation refrigerating film, and preparation method and application

    CN110372976A

  • Zirconia-doped alumina ceramic substrate and preparation process thereof

    CN111393151A

  • Water-based transparent glass heat insulation coating and preparation method thereof

    CN113801527A

  • Coated textile with all-day efficient passive radiation cooling function and preparation method thereof

    CN115323801A

Cited By

  • Diopside crystal glaze with radiation refrigeration function as well as preparation method and application of diopside crystal glaze

    CN121850368A

  • Radiation refrigeration ceramic tile and preparation method thereof

    CN122102516A

  • Radiation cooling ceramic tile and preparation method thereof

    CN122102516B

  • Radiation refrigeration ceramic tile with microporous structure and preparation method of radiation refrigeration ceramic tile

    CN122145198A